2017
DOI: 10.5435/jaaos-d-15-00661
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Fractures in Adults Treated With Internal Fixation: A Prospective Multicenter Chinese Cohort

Abstract: Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…The treatment of femoral neck fracture in young patients faces many challenges, and if clinicians fail to provide improper treatment, it may lead to catastrophic consequences for patients [2][3][4][5][12][13][14]. The proportion of patients with femoral neck fractures under 65 years who underwent total hip arthroplasty increased from 1.4-13.1% from 1999 to 2011 [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of femoral neck fracture in young patients faces many challenges, and if clinicians fail to provide improper treatment, it may lead to catastrophic consequences for patients [2][3][4][5][12][13][14]. The proportion of patients with femoral neck fractures under 65 years who underwent total hip arthroplasty increased from 1.4-13.1% from 1999 to 2011 [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 540 orthopedic surgeons, 78% of surgeons prefer to use multiple cannulated screws for the treatment of nondisplaced femoral neck fracture. For displaced fractures, multiple screws (46%) and sliding hip screws (SHS, 49%) were rst taken into consideration for the majority of orthopedic surgeons [12]. Most of the studies were reported higher rates of avascular necrosis, premature epiphyseal fusion, and heterotopic ossi cations after open reduction [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonunion was judged according to the criteria described by Dhar et al [14]. Femoral head necrosis was judged according to the standard of Slobogean et al [15]. According to Slobogean et al [16] definition of femoral neck shortening, the difference between the measured value on the affected side and the normal side of the pelvic orthotopic x-ray film was assessed as femoral neck shortening.…”
Section: Outcome Measurementmentioning
confidence: 99%
“…Nonunion was judged according to the criteria described by Dhar et al [14]. Femoral head necrosis was judged according to the standard of Slobogean et al [15]. According to Slobogean et al [16] definition of femoral neck shortening, the difference between measured value on the affected side and the normal side of pelvic orthotopic xray film was assessed as femoral neck shortening.…”
Section: Outcome Measurementmentioning
confidence: 99%